Cosmic black holes - from stellar to supramassive black holes in galaxies - Camenzind, M. (Annalen der Physik, 2006)
The collapse of massive stars produces the most bizarre objects in the Universe. In the last ten years, astronomers have been successfully searching for real black holes in the Universe. Black hole astrophysics began in the 1960s with the discovery of quasars and other active galactic nuclei (AGN) in distant galaxies. Already in the 1960s it became clear that the most natural explanation for the quasar activity is the release of gravitational energy through accretion of gas onto supermassive black holes. The remnants of this activity have now been found in the centers of about 50 nearby galaxies. BH astrophysics received a new twist in the 1970s with the discovery of the X‐ray binary Cygnus X‐1. The X‐ray emitting compact object was too massive to be explained by a neutron star. Today, about 20 excellent BH candidates are known in XRBs. On the extragalactic scale, more than 100,000 quasars have been found in large galaxy surveys. At the redshift of the most distant ones, the Universe was younger than one billion year. The most enigmatic black hole candidates identified in the last years are the compact objects behind the Gamma‐Ray Bursters. The formation of all these types of black holes is accompanied by extensive emission of gravitational waves. The detection of these strong gravity events is one of the biggest challenges for physicists in the near future.